Green fuel production: Processes applied to microalgae - Ana L. Gonçalves (2013)
The continuous increase in world energy demand will lead to an energy crisis due to the limited availability of fossil fuels. Furthermore, the use of this energetic resource is responsible for the accumulation of greenhouse gases in atmosphere that is associated with several negative effects on environment. Therefore, it is worth to search for different energy supplies that are renewable and environmentally friendly-carbon neutral fuel. Microalgae are photosynthetic microorganisms that can achieve high oil contents. This oil is suitable for producing biodiesel; thus, microalgae are considered a promising sustainable energetic resource that can reduce the dependence on fossil fuel. Biodiesel production from microalgae includes several steps, such as cell cultivation and harvesting, oil extraction and biodiesel synthesis. Although several attempts have been made to improve biodiesel yields from microalgae, further studies are required to improve biodiesel production rates and to reduce the associated costs. This review shows the recent developments on biodiesel production from microalgae, emphasizing two process concepts: (1) indirect route, in which, after a facultative cell wall disruption method, microalgal oil is recovered in an appropriate solvent and then converted into biodiesel through transesterification and (2) direct route, in which biodiesel is produced directly from the harvested biomass. High biodiesel yields are obtained when both routes are preceded by a cell wall disruption method. In the indirect route, it is possible to apply three different types of solvents to recover microalgal oil. Although there are several concerns about the application of organic solvents, the most promising and cost-effective alternative for lipid recovery is n-hexane. Comparing direct and indirect routes, this study demonstrates that although further studies are required to optimize biodiesel production from microalgae, the available information proposes that the direct route is the most efficient. (c) 2013 Springer-Verlag Berlin Heidelberg.